Vers une nouvelle édition des poèmes de Serlon de Bayeux - Marie-Agnès Lucas-Avenel; Edoardo D’Angelo (Tabularia)
In spite of the historical and literary interest of the satirical poems of Serlo of Bayeux, who was a witness of the capture of Bayeux by King Henry I, as well as a victim of the Gregorian reform and of the rapacity of the abbot of Saint-Étienne of Caen, his work is unknown or even forgotten by scholars. The number of the poems attributed to him varies greatly, because the canon of Bayeux had sometimes been identified with Serlo of Wilton or other poets like Marbode de Rennes. He is now recognized as the author of nine poems, which have not yet been published together. Most are available through the publication of Th. Wright, The Anglo-Latin Satirical Poets and Epigrammatists of the Twelfth Century (1872), which contains textual problems; we can add the articles of André Boutemy (1938) and of Rolf Lenzen (1990).   By way of an announcement of the next critical edition of the poems of Serlo of Bayeux, this article gives a brief presentation of each text and of its witnesses, a closer examination of the Quae monachi quaerunt to illustrate the principles that will be applied to the edition, and the establishment of a Serlonian “canon” based on six methodological elements tested on one of the most debated pseudo-Serlonian poems, the Pro corruptibili.